Influence of Roman Law on the Law of Obligations according to ABGB – the Comparison of Selected Contract Types - Miroslav Frýdek (Journal on European History of Law)
The article analyses an influence of Roman Law on modern civil law codifications. A Roman classification is studied in details. The present paper compares an influence of selected Roman law institutes on law of obligation according to ABGB.